RÜLFS CRAMP AND OTHER PAROXYSMAL DYSKINESIA - M. V. Selikhova; Z. Z. Zalyalova; N. I. Bogdanova; G. G. Avakyan; G. Houlden (Эпилепсия и пароксизмальные состояния)
Paroxysmal dyskinesia comprise a significant and fascinating part of movement disorders, which represent a diagnostic challenge for neurologists working on the borderlands of psychiatry and epilepsy. The current classification based on the relation of attacks to a movement is supported by the response to treatment and genetic difference. We reviewed clinical characteristics and the main advances in genetics of these unique, usually hereditary diseases. Clinical diagnosis remains the key to the treatment choice. Psychogenic causes are common in sporadic cases, but paroxysmal dyskinesia secondary to systemic or primary neurological disorders should not be missed and warrant careful investigation.